The soundtrack of criminal careers: On music, life courses and life stories - Rodríguez Goyes, David (Theoretical criminology, 2024)
Music is ubiquitous in contemporary societies, and criminologists are paying increasing attention to it, asserting that it takes antisocial, prosocial and anti-establishment forms regarding criminality. Established approaches provide vital ways to understand the relationship of music and crime, but criminologists have yet to theorise the fluidity of music's roles for those who have committed criminalised acts. The life-story interviews we conducted with prisoners in Latin America reveal that music's role in people's lives changes over the course of their lives in complex ways. It also frames and influences the way they talk about their own histories. Informed by repeat interviews with four prisoners, we suggest including the concepts of life courses and life stories to facilitate understanding the complexity and multi-dimensionality of the relationship between crime and music. We also demonstrate and discuss how life courses and life stories are intertwined.